1993
DOI: 10.1002/1097-0142(19930115)71:2<287::aid-cncr2820710203>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Unresectable nonmetastatic squamous cell carcinoma of the esophagus managed by sequential chemotherapy (cisplatin and bleomycin) and radiation therapy

Abstract: Background. For patients with unresectable non‐metastatic squamous cell carcinoma of the esophagus (SCCE), the conventional treatment has been radiation therapy (RT). Because RT alone is unsatisfactory, there has been increasing interest in including chemotherapy (CT) in the management of these patients. Methods. Twenty‐five previously untreated patients with unresectable nonmetastatic SCCE were treated with sequential CT and RT. CT consisted of cisplatin 35 mg/m2/day for 3 days plus bleomycin 15 mg/ day for 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…The results of that trial demonstrated a very low local failure rate of 25%, a 5-year actuarial survival rate of 30%, and a 5-year actuarial local relapse-free survival rate of 70% for patients with Stage I disease. However, in a study of 30 patients with clinical Stage I-III disease, John et al (15) reported (16). RTOG trial 85-01 (1) established that a radiation dose of 50 Gy is appropriate for patients with esophageal cancer treated with simultaneous cisplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of that trial demonstrated a very low local failure rate of 25%, a 5-year actuarial survival rate of 30%, and a 5-year actuarial local relapse-free survival rate of 70% for patients with Stage I disease. However, in a study of 30 patients with clinical Stage I-III disease, John et al (15) reported (16). RTOG trial 85-01 (1) established that a radiation dose of 50 Gy is appropriate for patients with esophageal cancer treated with simultaneous cisplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Fünf Studien [20,34,38,44,47] berichten über > 10% WHO Grad-3/4-Toxizitäten und drei [34,38,49] über therapiebedingte Todesfälle. Dies zeigt ein Überblick über elf Studien von 1990 bis 2000 mit Kollektiven zwischen 22 und 65 Patienten, die mindestens 75% fortgeschrittene Ösophaguskarzino-me enthalten hatten [5,9,20,25,34,38,43,45,48,49,53]. Unsere eigenen Ergebnisse können hier zwanglos eingeordnet werden.…”
Section: Diskussionunclassified